Public Enterprise in Mixed Economies : Some Macroeconomic Aspects - Gray, Clive; Floyd, Robert; Short, R. (Washington, D.C. : International Monetary Fund, 1984)
This volume, written by Robert H. Floyd, Clive S. Gray, and R.P. Short, contains three papers dealing with various aspects of the public enterprise sector and the impact that these may have on macroeconomic analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet